2022
DOI: 10.5397/cise.2022.00885
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical investigation of arm position on deforming muscular forces in proximal humerus fractures

Abstract: Background: Muscular forces drive proximal humeral fracture deformity, yet it is unknown if arm position can help mitigate such forces. Our hypothesis was that glenohumeral abduction and humeral internal rotation decrease the pull of the supraspinatus and subscapularis muscles, minimizing varus fracture deformity.Methods: A medial wedge osteotomy was performed in eight cadaveric shoulders to simulate a two-part fracture. The specimens were tested on a custom shoulder testing system. Humeral head varus was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…At our tertiary hospital, we frequently encounter cases of failed conservative treatment for PHFs due to suboptimal immobilization position. Upon reviewing previous studies 14 , 15 , 19 , 25 , 26 , many kinds of slings or braces that achieve internal rotation of the shoulder have been conventionally utilized for conservative treatment of PHFs. In recent studies 20 , 21 , 27 , however, there has been a proposal to immobilize the arm in the neutral position in PHFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At our tertiary hospital, we frequently encounter cases of failed conservative treatment for PHFs due to suboptimal immobilization position. Upon reviewing previous studies 14 , 15 , 19 , 25 , 26 , many kinds of slings or braces that achieve internal rotation of the shoulder have been conventionally utilized for conservative treatment of PHFs. In recent studies 20 , 21 , 27 , however, there has been a proposal to immobilize the arm in the neutral position in PHFs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies 20 , 21 , 27 , however, there has been a proposal to immobilize the arm in the neutral position in PHFs. On the other hand, Chalmers et al 14 , 15 suggested shoulder abduction and internal rotation for the immobilization position in surgical neck fractures to decrease deformation by muscular force. As described in previous studies, there is still no consensus on optimal immobilization position for conservative treatment in different types of PHFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sports-related injuries have been reported in hockey, lacrosse, baseball, football, wrestling, judo, and soccer [2][3][4]. The most common mechanism of injury involves remnant subscapularis apophyseal plate avulsion while some are a combination of abduction, external rotation, and extension in the shoulder [2][3][4][5][6]. The incidence of these injuries has increased among younger patients with increased participation in athletic activities.…”
Section: Introductionmentioning
confidence: 99%
“…There has been little research on the immobilization position of the affected arm with consideration of fracture type. In the few studies touching on this topic, most of the focus was on varus collapse associated with SN fracture type [12,13]. Among patients referred to our hospital, there have been many cases where initial suboptimal immobilization positioning worsened the condition compared to the initial fracture.…”
Section: Introductionmentioning
confidence: 99%